The Dynamics of Organizational Proximity - Monge, Peter R.; Rothman, Lynda White; Eisenberg, Eric M.; Miller, Katherine I.; Kirste, Kenneth K. (Management Science, 1985)
The proximity among people in an organization is known to exert considerable influence on a variety of organizational outcomes such as performance, stress, and job satisfaction. Early research on proximity in organizations studied pairs of people in job locations that were at fixed distances (e.g., keypunch operators at their work stations). This research procedure ignores three critical features of organizational life. First, people are simultaneously proximate to everyone else in their organization. Second, this proximity changes throughout the day as people move about the organization. Finally, the opportunity and obligation for communication that people perceive by being physically close to others is often more important than the actual physical distance. The present paper develops a definition of organizational proximity that accounts for these previous limitations. Specifically, organizational proximity is defined as two or more people being in the same location where there is both the opportunity and psychological obligation for face-to-face communication. This measure, when aggregated across all people in an organization, provides a single value of how concentrated people are in the various locations of the firm. Further, given the proper data collection techniques, it reveals the degree to which organizational proximity changes throughout the workday and workweek. On the basis of this definition, research was conducted which examined the organizational proximity among employees in a research and development firm for each 15-minute interval of a typical workweek. Two major findings were obtained. First, the level of organizational proximity changed considerably during the course of a typical day, with peaks during the late morning and early afternoon and valleys during the early morning, lunch, and late afternoon hours. Second, the pattern was highly consistent from day-to-day. This consistency permitted the development of a model which enables accurate prediction of the level of organizational density for any time period during any day of the workweek. There are several rather interesting managerial implications in these results. First, they support Peters and Waterman's (Peters, T. J., R. H. Waterman. 1982. Search of Excellence: Lessons from America's Best-Run Companies. Harper & Row, New York, 3–26, 119–155, 200–234.) recent recommendation of “management by wandering around,” since that technique maximizes a manager's proximity to employees. Second, the results suggest managerial and electronic alternatives to traditional forms of communication such as face-to-face meetings and phonecalls. Third, they imply alternative strategies for managing the daily fluctuations in availability of people and communication that result from differences and changes in organizational proximity.